A 45,000-mol-wt protein from unfertilized sea urchin eggs severs actin filaments in a calcium-dependent manner and increases the steady-state concentration of nonfilamentous actin (The Rockefeller University Press, 1984)
A 45,000-mol-wt protein has been purified from unfertilized sea urchin (Strongylocentrotus purpuratus) eggs. The isolation scheme includes DEAE cellulose ion-exchange chromatography, gel filtration, and hydroxylapatite chromatography. The homogeneity of the isolated protein is greater than 90% by SDS PAGE. The 45,000-mol-wt protein reduces the viscosity of actin filaments in a Ca2+-dependent manner. The free calcium concentration required for the activity of this protein is in the micromolar range. Electron microscopic studies reveal that the formation of short filaments parallels the decrease in viscosity. Energy transfer and sedimentation experiments indicate a net disassembly of actin filaments and an increase in the steady-state nonfilamentous actin concentration in the presence of Ca2+ ions and the 45,000-mol-wt protein. The increase in the steady-state nonfilamentous actin concentration is proportional to the amount of 45,000-mol-wt protein added. The actin molecules disassembled by the addition of the 45,000-mol-wt protein are capable of polymerization.